A long lifetime switch-on iridium(iii) chemosensor for the visualization of cysteine in live zebrafish. Issue 24 (22nd February 2016) - Mao, Zhifeng; Wang, Modi; Liu, Jinbiao; Liu, Li-Juan; Lee, Simon Ming-Yuen; Leung, Chung-Hang; Ma, Dik-Lung
Abstract : A long lifetime iridium(iii ) complex chemosensor1 for cysteine detection has been synthesized. Abstract : A long lifetime iridium(iii ) complex chemosensor1 for cysteine detection has been synthesized. The luminescence signal of1 could be recognized in strongly fluorescent media through time-resolved emission spectroscopy (TRES). The detection of cysteine in a living zebrafish was demonstrated.